2013
DOI: 10.1016/j.neuropsychologia.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparable mechanisms of working memory interference by auditory and visual motion in youth and aging

Abstract: Intrasensory interference during visual working memory (WM) maintenance by object stimuli (such as faces and scenes), has been shown to negatively impact WM performance, with greater detrimental impacts of interference observed in aging. Here we assessed age-related impacts by intrasensory WM interference from lower-level stimulus features such as visual and auditory motion stimuli. We consistently found that interference in the form of ignored distractions and secondary task i nterruptions presented during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 67 publications
3
27
2
1
Order By: Relevance
“…For example, we did not find a greater impact of distractions and interruptions in the auditory modality in older relative to younger adults (Mishra et al, 2013). Older adults also perform equivalently to younger adults in a multisensory setting, even when the audiovisual stimulus content is incongruent/conflicting across the two sensory domains (Mishra and Gazzaley, 2013).…”
Section: External Interference Resolution Across the Lifespancontrasting
confidence: 64%
See 1 more Smart Citation
“…For example, we did not find a greater impact of distractions and interruptions in the auditory modality in older relative to younger adults (Mishra et al, 2013). Older adults also perform equivalently to younger adults in a multisensory setting, even when the audiovisual stimulus content is incongruent/conflicting across the two sensory domains (Mishra and Gazzaley, 2013).…”
Section: External Interference Resolution Across the Lifespancontrasting
confidence: 64%
“…In contrast, neural activity to interruptions, which served as stimuli for a secondary discrimination task, was enhanced. Recently, we replicated these findings for intrasensory interference during auditory WM (Mishra et al, 2013). Using fMRI-based functional connectivity analyses, Clapp et al (2011) further revealed that at the onset of interruptions, connectivity in a visual (visual association cortex, VAC)–prefrontal (middle frontal gyrus, MFG) memory maintenance network was disrupted and dynamically reallocated to the attended interruptor.…”
Section: External Interference Resolution Across the Lifespansupporting
confidence: 57%
“…In a paradigm previously described (Berry et al, 2009, Mishra et al, 2013a), participants were presented with three different tasks randomized across six blocks, with two blocks per task. There were two delayed recognition WM tasks, one with no interference (NI) during the WM delay and one with an interrupting stimulus (IS) during the WM delay that required attention.…”
Section: Methodsmentioning
confidence: 99%
“…Working memory involves the temporary storage and manipulation of information, necessary for a wide range of cognitive activities, whereas inhibitory control is the ability to suppress cognitive interference from irrelevant information that interferes with the task in hand . Cognitive interference occurs when new learned materials cause disturbance in memory retrieval . Proactive interference is when old memories inhibit retrieval of new memories, whereas retroactive interference is when new memories prevent recovery of old memories.…”
Section: Introductionmentioning
confidence: 99%
“…11 Cognitive interference occurs when new learned materials cause disturbance in memory retrieval. 12 Proactive interference is when old memories inhibit retrieval of new memories, whereas retroactive interference is when new memories prevent recovery of old memories.…”
Section: Introductionmentioning
confidence: 99%